Primerjava triboloških lastnosti mineralnih in repičnih mazalnih olj - Arnšek, Aleš (Strojniški vestnik, 2001)
In the present work, the coefficient of friction, wear, scuffing-load capacity, pitting resistance and normal sliding wear of rapesed-based oils were evaluated and the results compared with the corresponding mineral-based oil. The wear scar diameters were examined by using the scanning electron microscope with energy dispers X-ray analyzer (SEM-EDXS). The test results show similar or even better lubrication properties of rapeseed-based oils compared with a commercially available mineral based oil. The rapeseed-based oils exhibit lower coefficient of friction in the boundary lubrication regime, equivalent scuffing wear protection, better pitting resistance and good lubrication properties at high load - slow speed conditions.
Keywords: olja repična; SEM-EDXS; lastnosti maziv; lastnosti mehanske; maziva; repično olje; mehanske lastnosti; mazanje